Dynamic analysis of different resource allocations: Implications for resource orchestration management of strategic alliances - Zhao, Jianyu; Xi, Xi; Wang, Shanshan; Gong, Caiyan (Computers & Industrial Engineering, 2021)
• Use Evolutionary Game to clarify the applicability of various resource allocations. • Expose the different key factors affecting the roles of resource allocations. • Breadth resource allocations have advantage when alliance environment is ambiguous. • Targeted resource allocations enhance the benefits if commercial prospects are clear. A lack of understanding regarding the roles and applicability of different resource allocations has become the underlying reason for the failure of resource efforts. Therefore, it is of important practical significance to examine the effects of different resource allocations and their impacts on the development of strategic alliances. Based on the development intentions of technological innovation cooperation and social capital accumulation, our study distinguished four patterns of resource allocation and viewed them as dynamic processes instead of unchanging decision results, using simulation from evolutionary game theory to explore the roles and applicability of various resource allocations by exposing their stability under different constraint situations. Our results indicate that, first, the randomly-oriented resource allocation has the highest probability of being unstable, while the knowledge-embedded resource allocation has the lowest probability. Second, randomly-oriented resource allocation can lead an alliance to become a pure technology or social alliance; relationship-oriented resource allocation is sensitive to opportunistic behavior, but more favorable to innovation diffusion; cooperation-oriented resource allocation is mainly affected by resource cost, and more suitable for firms with strong innovation intentions; and knowledge-embedded resource allocation is conducive to reducing the uncertainty and enhancing the configuration success rates. Third, the breadth of the resource allocation increases the probability of successfully configuring resources, and the strategic decision to switch from broad resource allocation to a targeted one may increase the extraneous benefits of firms when the development prospects are clear.
Keywords: Réservé UdeM

Dynamic analysis of different resource allocations: Implications for resource orchestration management of strategic alliances - Zhao, Jianyu; Xi, Xi; Wang, Shanshan; Gong, Caiyan (Computers & Industrial Engineering, 2021)
• Use Evolutionary Game to clarify the applicability of various resource allocations. • Expose the different key factors affecting the roles of resource allocations. • Breadth resource allocations have advantage when alliance environment is ambiguous. • Targeted resource allocations enhance the benefits if commercial prospects are clear. A lack of understanding regarding the roles and applicability of different resource allocations has become the underlying reason for the failure of resource efforts. Therefore, it is of important practical significance to examine the effects of different resource allocations and their impacts on the development of strategic alliances. Based on the development intentions of technological innovation cooperation and social capital accumulation, our study distinguished four patterns of resource allocation and viewed them as dynamic processes instead of unchanging decision results, using simulation from evolutionary game theory to explore the roles and applicability of various resource allocations by exposing their stability under different constraint situations. Our results indicate that, first, the randomly-oriented resource allocation has the highest probability of being unstable, while the knowledge-embedded resource allocation has the lowest probability. Second, randomly-oriented resource allocation can lead an alliance to become a pure technology or social alliance; relationship-oriented resource allocation is sensitive to opportunistic behavior, but more favorable to innovation diffusion; cooperation-oriented resource allocation is mainly affected by resource cost, and more suitable for firms with strong innovation intentions; and knowledge-embedded resource allocation is conducive to reducing the uncertainty and enhancing the configuration success rates. Third, the breadth of the resource allocation increases the probability of successfully configuring resources, and the strategic decision to switch from broad resource allocation to a targeted one may increase the extraneous benefits of firms when the development prospects are clear.
Keywords: Réservé UdeM